Caribbean cultures and mass communication technology in the 21st century. - Brown, Aggrey (1990)
Cites some of the salient characteristics of contemporary mass media technologies, and suggests that they are potent information transmitting technologies. Points out that the concept of cultural imperialism in the region is a misdiagnosis of the situation since Caribbean citizens are willing consumers of both hardware and software. Lists matters to be addressed in formulationg and implementing regional and national information/communication policies which will allow meaningful participation in the evolution of global culture through the visual media.